Self-determinable Development of Small Islands - Ishihara, Masahide; Hoshino, Eiichi; Fujita, Yoko (Springer Nature Singapore : Imprint: Springer, 2016)
This book aims to clarify the present situation of the relations between small island countries and territories on the one hand and the great powers, mainland areas, and mega-islands on the other, and explores how small island countries and territories preserve and build their identity under globalization. This book is divided into five parts. The first part presents papers on issues that are related to Okinawa: the American military presence, the formation of a global human network, and the history of and language revitalization in Okinawa. The second part includes papers on security in East Asia and the Pacific Region: the history of and present issues in international relations within the South and East China Sea areas. The third part presents papers on economic issues and social developments on small islands. The fourth part deals with ocean policies and marine resource management in the Pacific Region by the United States, Australia, and Japan. Finally, the fifth part presents papers on the revitalization of three indigenous languages. All the chapters of the book are based on the achievements of the research project "Towards New Island Studies: The Ryukyus as an academic node between East Asia and Oceania" conducted by the International Institute for Okinawan Studies at the University of the Ryukyus. This 5-year project was funded by the Japanese Ministry of Education, Culture, Sports, Science and Technology and aimed to contribute academically to the creation of sustainable and self-determinable societies in small island regions. This work will be extremely useful and informative for readers in small island countries and territories and for researchers who are interested in small island issues to understand the current situation and who wish to consider effectual and feasible solutions.